197Au(n,xn) reactions at The Svedberg Laboratory high-energy neutron facility in Uppsala - Kalamara, A.; Vlastou, R.; Kokkoris, M.; Stamatopoulos, A.; Passoth, E.; Mattera, A.; Lantz, M.; Rakopoulos, V.; Prokopiev, A.; Majerle, M. (HNPS Advances in Nuclear Physics, 2019)
Cross section measurements for the197Au(n,xn) reactions have been performed at The Svedberg Laboratory (TSL) high-energy neutron facility in Uppsala,Sweden. The 45.6 and 58.3 MeVquasi-monoenergetic neutron beams were produced by means of the 7Li(p,n) reaction and were monitored with thin-film breakdown counters (TFBCs). After the end of the irradiations, the activity induced by the neutron beams in the targets and in reference foils, has been measured by a HPGe detector. In order to determine the cross sections of the (n,xn) reactions, the spectral neutron flux distribution is needed, thus the characterization of the beam is of major importance. Therefore, simulations that take into account the whole experimental setup of the irradiation have been performed with the use of MCNP5 code and the results are presented in this work. Currently, further analysis of the data is in progress.